PENINGKATAN KETERAMPILAN MENULIS PUISI MENGGUNAKAN MODEL PICTURE AND PICTURE DI SEKOLAH DASAR - Poniem, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstrakThe common problem of this research is to find out whether the application of picture and picture model can improve the poetry writing skills of third grade students of Â SDN 24 Pontianak Tenggara. The general purpose of this research is to describe the application of picture and picture model that can improve the poetry writing skill of third grade students of SDN 24 Pontianak Tenggara. The method that used in this research was descriptive method with a form of classroom action research. The subject in this research were 28 students of class III.. The data collection techniques used in this research are the observation sheet and the document inspection sheet. Data analysis in this research was conducted between researcher and observer collaboration. This research result: (1) The teachers planning learning ability is very good because on cycle I is 3,01 in cycle II is 3,26 and in cycle III become 3,44. (2) The teachers doing learning ability is very good because on cycle I is 2,99 in cycle II is 3,23 and in cycle III become 3,64. (3) Ability to write poetry better use picture and picture model because in cycle I mean student value is 53,85, at cycle II 70,52 and at cycle III increased to 76,50.Keywords: Writing Skil, Picture and Picture Model.